Pendampingan Turnamen Sepakbola Putri Mahasiswa Dehasen Bengkulu - Ertanto, Dody; Putra, Dwingki Marta (Universitas Dehasen Bengkulu, 2024)
Dehasen University is one of the private universities in Bengkulu City. Dehasen University has a Physical Education Study Program, which is where competent and outstanding PJOK teachers are born. In Physical Education there are many courses that include both practical and non-practical, one of the practical courses is the football course, football courses are always available in every 1st and 2nd semester, with so many classes in the Physical Education Study Program that competitions are held between classes . It is hoped that holding competitions or tournaments between classes will have a good impact on students, especially students of the Physical Education Study Program. In this tournament, students will manage the competition so that it can run smoothly and the tournament held by the Physical Education Study Program will be held on the football field. Pancasila Islamic Boarding School involving Physical Education Study Program Lecturers. so that community service was carried out by Dehasen University lecturers with the theme: Mentoring the Dehasen Bengkulu Student Women's Football Tournament.